The impact of organic amendments on soil properties under mediterranean climatic conditions - Hueso-González, Paloma; Martínez-Murillo, Juan Francisco; Ruiz-Sinoga, José Damián (EGU, 2016)
Soil erosion and unsustainable land use produce adverse effects on SOC content. Soil management techniques and corrections can be applied for soil recovery, especially, with afforestaion purposes. This study presents the short term effects on the application of different treatments on soil properties for soil included in several sets of closed plots located in the experimental area of Pinarillo (Nerja, Spain). The analysed soil properties were: PH, EC, organic carbon, total nitrogen and total carbon. In order to verify possible differences, we applied the test of Mann-Whitney U in corroboration with the previous homogeneity test of variance.
Keywords: Deforestación; Ecosistemas mediterráneos; Soil degradation; Soil properties; Soil amendments